Gamification in the academic performance of the mathematics course in incoming students undergraduate from a private university in Lima (LACCEI, 2024)
The objective of this research work was to evaluate and analyze the results of introducing an innovative methodology such as gamification that helps to improve the teaching and learning process in higher education students and, thus, improve the academic performance of students prioritizing three aspects. important: interest, active participation, and continuous learning Leaving behind the systematic academic components that are based on memorization or the meaningless search for a good grade without the correct learning of the basic foundations within the student's professional training. This research is quantitative, in which we worked with university students from the leveling courses of mathematics and basic mathematics applied to different engineering careers. Initially, the students were evaluated, through the application of a survey to identify the reasons for their low academic performance, in this aspect it was observed that 72.5% of the student’s state that they had a bad foundation in their respective schools. Then, the gamification tools were implemented in the description of the topics proposed in the syllabus and the influence on academic performance was analyzed, this implementation resulted in students being able to improve their academic performance, and 12.3% of students They were more motivated when carrying out the activities. Finally, the training was carried out for the teachers explaining how to use the gamification tools and how the evaluation should be carried out on the students, at this point it was observed that some teachers were unaware of technological tools to incorporate into the learning process of the students. , but at the same time, they showed concern about updating themselves on the use of Tics and above all how to incorporate them into their class sessions.